Piezosurgery versus rotary instrument in mandibular third molar surgery - Yadav, Deepak; Karki, Bijay; Mishra, Ravish; Kandel, Laxmi; Ali, Shahid (Journal of Chitwan Medical College, 2024)
Background: The purpose of this study is to compare the effect of surgical removal of third molar by using piezosurgery versus rotary instrument in terms of pain, swelling, infection, and trismus along with operative time difference between the procedures.Method: The study was designed as an observational prospective study, and implemented on patients who required surgical removal of impacted mandibular third molar visiting the Department of Oral and Maxillofacial Surgery, UCMS College of Dental Surgery, Bhairahawa, Nepal.  Patients were divided into two equal groups, Gr A: Piezosurgery, and Gr B: Rotary instrument. Variables measured were intraoperative time, pain, swelling, mouth opening, and infection on the 1st, 3rd, and 7th postoperative days. A p-value